Biopolitical Other - Duško Petrović ([sic], 2011)
In the beginning of this short text, which will discuss the question of the postmodern Other, I will propose that the post-Other, or Other in the postmodern condition, be called the biopolitical Other. The thesis is as follows: when we think about the question of the Other in the contemporary condition, which for want of a better definition and following Lyotard could be named postmodern, the dominance of the biopolitical Other can be observed on a global scale. In approaching the question of the biopolitical Other, I will not follow the path usual in problematizing the biopolitical. When thinking about biopolitics, the usual path begins with the creator of the term, Foucault, to theorists who adopted and somewhat changed its original meaning, such as Agamben and others. I will approach the term of the biopolitical Other using terms borrowed from political theory which problematizes notions such as State, sovereignty, Nation-State, Law, international Law. I will begin the analysis starting with some aspects of the notion of sovereignty, problematized in the 1920s by Carl Schmitt and relate it to the notion of biopolitics, recently popularized by Agamben. But the path to the notion of biopolitics will be slightly different than Agamben's.